TRAINING OF BASIC PROFICIENT COURSE (KMD) FOR KWARTIR SCOUT LEADERS BRANCH WEST BANDUNG REGENCY IN INCREASING COMPETENCE THROUGH ADULT EDUCATION METHODS - Hikmah Faizal; Nandang rukanda (IKIP Siliwangi Bandung, 2024)
The background of doing this research is motivated by the statement that in the 2013 curriculum extracurriculars that are required for students to follow are scouting extracurricular scouts are important so that scout coaches must have good competence so that students can develop their potential. The purpose of this study is that researchers can find out how the Basic Advanced Course (KMD) training for Scout Leaders Kwartir Branch of West Bandung Regency in improving competence through adult education methods. The theories used are training theory, adult education, KMD theory, and scouting and competency theory.The method used in this research is descriptive qualitative with a sample of two committee members and eight participants. Data collection techniques using interviews and observation. The results of the research on Basic Advanced Course Training (KMD) for Scoutmasters Kwartir West Bandung Regency in increasing competence through adult education methods that the training went well according to plan and the trainees received benefits that could be applied when they went to school. In addition, the competence of the participants or scout coaches becomes more developed and can foster students in developing their potential when participating in extracurricular activities.